2022
DOI: 10.1038/s41531-022-00428-2
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in dementia with Lewy bodies

Abstract: Gut microbiota and fecal bile acids were analyzed in 278 patients with α-synucleinopathies, which were comprised of 28 patients with dementia with Lewy bodies (DLB), 224 patients with Parkinson’s disease (PD), and 26 patients with idiopathic rapid eye movement sleep behavior disorder (iRBD). Similarly to PD, short-chain fatty acids-producing genera were decreased in DLB. Additionally, Ruminococcus torques and Collinsella were increased in DLB, which were not changed in PD. Random forest models to differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 118 publications
1
13
0
Order By: Relevance
“…Our recent study has shown that the abundance of SCFA-producing bacteria is decreased, and that of Akkermansia is increased in DLB 80 , as has been observed in PD 62 . In addition, the abundance of Ruminococcus torques and Collinsella is increased in DLB, but not in PD.…”
Section: Gut Microbiota In Dementia With Lewy Bodies (Dlb)supporting
confidence: 63%
See 3 more Smart Citations
“…Our recent study has shown that the abundance of SCFA-producing bacteria is decreased, and that of Akkermansia is increased in DLB 80 , as has been observed in PD 62 . In addition, the abundance of Ruminococcus torques and Collinsella is increased in DLB, but not in PD.…”
Section: Gut Microbiota In Dementia With Lewy Bodies (Dlb)supporting
confidence: 63%
“…Thus, the mitigation of neuroinflammation is likely to be effective in the substantia nigra, but not in the cerebral cortex, where neuroinflammation may not critically aggravate neuronal cell death. DLB generally develops at the age of above 65 years 128 , and its average is higher than that of PD 80 , 128 . The lack of PD symptoms in older patients with DLB is consistent with the notion that dopaminergic neuronal cell death due to neuroinflammation at the substantia nigra is not critical in DLB.…”
Section: The Causal Association Of Gut Microbiota With Pdmentioning
confidence: 93%
See 2 more Smart Citations
“…Among them, Acetatifactor is a strictly anaerobic bacteria that can produce acetate and butyrate at a certain ratio in the gut, [ 58 ] whereas Blautia is known as a SCFA‐producing bacteria. [ 59 ] Meanwhile, Parasutterella has been reported to be positively correlated to fatty‐acid biosynthesis and β‐cell failure in obesity and type 2 diabetes cohorts. [ 60 ] Nevertheless, the species in this guild and the functionalities of the guild should be further clarified.…”
Section: Discussionmentioning
confidence: 99%